Repeating and replicating Sinan throughout the ages: continuity, nostalgia, or aesthetic consensus? - Metin, Alper (Aesthetica Preprint, 2024)
After his death in 1588, the architectural norms established during the time of Sinan largely persisted until the 1730s. The eighteenth century established its own aesthetic canons putting together local and Western forms. Throughout the nineteenth century, a long ‘interludium’ took place, while the Ottoman architects were experimenting with new forms deriving mostly from foreign (or intercultural) sources. With the emergence of a proto-nationalistic architectural Romanticism at the beginning of the twentieth century, the forms of the so-called Classical Age were included once again in the vocabulary of the late-Ottoman and early Republican architects. But it was only in 1945, more than two decades after the foundation of the Turkish Republic in 1923 that the references to the age of Sinan gained a new momentum, and more importantly, a more precise direction. Over the last seven decades, an almost massive production of replicas has transformed Sinan into into a sort of national territory marker all over the country, permeating even the most remote contexts where he never set foot. What was different, then, between these historical phases, and what has been happening from 1945 to our day? For how long was Sinan’s direct influence active, and how did it dissipate? Are the replicas of the last decades copies with their own historicity? This essay will try to explore the multiple afterlives of Sinan’s forms focusing on the mosque architecture.